2016
DOI: 10.1136/neurintsurg-2016-012421
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive analysis of intra-arterial treatment for acute ischemic stroke due to cervical artery dissection

Abstract: ObjectiveThe safety and efficacy of intra-arterial treatment (IAT) in patients with acute ischemic stroke (AIS) due to cervical artery dissection (CeAD) has not been formally studied. The purpose of this study was twofold: first, describe a large series with CeAD treated with IAT; second, analyze outcomes with CeAD receiving IAT versus (a) CeAD not treated with IAT, (b) CeAD receiving intravenous thrombolysis (IVT) alone, and (c) non-CeAD mechanism of AIS receiving IAT.DesignDemographics, clinical characterist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 36 publications
3
26
0
Order By: Relevance
“…In fact, other reports on EVT in CAD-related AIS with mTICI 2b-3 more than 80% had better clinical outcomes than our series. [13][14][15] This is consistent with previous studies reporting a clear relation between early recanalization and good clinical outcome. 31 Finally, EVT patients had a lower median (pc-)ASPECTS on admission CT than the other groups.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In fact, other reports on EVT in CAD-related AIS with mTICI 2b-3 more than 80% had better clinical outcomes than our series. [13][14][15] This is consistent with previous studies reporting a clear relation between early recanalization and good clinical outcome. 31 Finally, EVT patients had a lower median (pc-)ASPECTS on admission CT than the other groups.…”
Section: Discussionsupporting
confidence: 92%
“…12 There are limited data available on EVT in AIS due to CAD from case series and observational studies. [13][14][15][16][17][18][19][20][21][22][23][24] Haussen et al collected 21 CAD-related AIS treated by EVT and compared them to 133 IVT patients pooled from previous studies in the literature. 14 Jensen et al published a retrospective single-center study that included 161 patients with stroke and CAD, 24 treated with mechanical thrombectomy and 137 with medical therapy (in this second group, only 11 received IVT).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies reported endovascular treatment for cerebral ischemia caused by embolism derived from cervical ICA dissection. 7,8) According to a review published by Hoving et al, the results of recanalization therapy to treat embolic intracranial arterial occlusion were favorable. 2) There have been only a few case reports on intracranial arterial occlusion related to intracranial ICA dissection.…”
Section: Disclosure Statementmentioning
confidence: 99%
“…Antiplatelets or anticoagulants are usually recommended to prevent primary or recurrent ischemic events. However, surgical or endovascular treatments may be used in patients with persistent symptoms of ischemia despite optimum medical treatment, or subarachnoid hemorrhage [6][7][8].…”
Section: Introductionmentioning
confidence: 99%